2012
DOI: 10.1088/0967-3334/33/2/n11
|View full text |Cite
|
Sign up to set email alerts
|

On the resolution of ECG acquisition systems for the reliable analysis of the P-wave

Abstract: The analysis of the P-wave on surface ECG is widely used to assess the risk of atrial arrhythmias. In order to provide reliable results, the automatic analysis of the P-wave must be precise and reliable and must take into account technical aspects, one of those being the resolution of the acquisition system. The aim of this note is to investigate the effects of the amplitude resolution of ECG acquisition systems on the P-wave analysis. Starting from ECG recorded by an acquisition system with a less significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The ECG signals were acquired from leads II, aVF and V1 at a sampling rate of 1000 Hz and 16-bit resolution over an amplitude range of ± 10 mV. These time and amplitude resolutions have proven to be recommended for P-wave analysis (Censi et al 2012). Only lead V1 was considered in the study because P-waves were most visible in this lead.…”
Section: Delineation Of the P-wavementioning
confidence: 99%
“…The ECG signals were acquired from leads II, aVF and V1 at a sampling rate of 1000 Hz and 16-bit resolution over an amplitude range of ± 10 mV. These time and amplitude resolutions have proven to be recommended for P-wave analysis (Censi et al 2012). Only lead V1 was considered in the study because P-waves were most visible in this lead.…”
Section: Delineation Of the P-wavementioning
confidence: 99%
“…According to [ 105 ], due to the lack of points available in ECG signals, signals with low sampling frequency are usually inefficient for ECG matching purposes when methods such as cross-correlation, percentage root-mean-square deviation, and wavelet distance measurement are used. As such, the low sampling frequencies used in old commercial systems (e.g., 128 Hz) usually need a reinterpolation of data [ 106 ]. There are already some studies that developed enhancement techniques to increase the number of samples of a given ECG data from low sampling frequency recordings [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…This advancement has provided new insights and has shown that techniques to reduce noise are effective in clinical settings. In [ 106 ], the authors investigated the effects of the amplitude resolution of ECG acquisition systems on the P-wave analysis. Results proved that at lower bit resolutions, the percentage error is higher than 40%, meaning that almost half of the results are different from the ones obtained with the highest resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effect of confounding factors such as age, gender or heart rate on P-wave features [28] cannot be controlled in the study. Second, the ECGs were sampled at 128 Hz, which hinders an accurate P-wave characterisation [29]. Finally, only 30 min-length ECG intervals were provided, thus turning impossible the analysis of longer time intervals before PAF onset, such as the presented in this study.…”
Section: Discussionmentioning
confidence: 99%